Potential of nanotechnology-based nanomaterials and biochar for tofu wastewater filtration: A review on clean water sustainability - Imanuel, Dionezra Bagus; Zain, Faatin Nisriinaa; Celesta, Belvannia Levina; Muna, Mochammad Choiril (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Water pollution, driven by industrial activities and population growth, increasingly contaminates water sources, threatening clean water supply. Tofu wastewater, rich in organic pollutants, exacerbates this issue, highlighting the need for sustainable, effective water treatment solutions. Methods: This study uses a literature review method, analyzing journals, articles, and scientific publications to explore nanomaterials and biochar for efficient tofu wastewater treatment and improving water quality in Semarang City. Findings: The filtration system using biochar, CNT, TiO₂, and ZVI significantly reduces contaminants in water, enhancing water quality. Each material contributes uniquely, improving adsorption, photocatalysis, and overall filtration efficiency for heavy metals and organic compounds. Carbon nanotubes (CNTs), zero-valent iron (ZVI), and titanium dioxide (TiO2) exhibit high efficiency in environmental remediation, offering cost-effective, sustainable solutions despite challenges like toxicity and mobility. The study demonstrates the potential of nanomaterials like CNTs, ZVI, and TiO2 for enhanced environmental remediation, particularly in wastewater treatment. Their synergistic use improves contaminant removal, offering sustainable solutions with significant efficiency gains. Conclusion: In conclusion, integrating nanotechnology and biochar for tofu wastewater treatment presents a sustainable, scalable solution that advances both environmental remediation and technological innovation, aligning with SDGs and enhancing water quality management efforts. Novelty/Originality of this article: The novelty lies in combining nanomaterials and biochar for efficient tofu wastewater treatment, enhancing filtration and sustainability in water quality management.